Makna Simbolik Liang Erong Bagi Masyarakat Tana Toraja - Saputra, Indrikal; Syarif, Erman; Abbas, Ibrahim (LaGeografia, 2020)
Cultural diversity in Indonesia is something that cannot be denied, which is caused by the geographical conditions of the Indonesian territory. The continuity and development of local culture needs to be preserved and avoided from obstacles. This study aims to determine: 1). Form of liang erong, especially the people of Tana Toraja. 2). The meaning of the carvings of each type of liang erong, especially the Tana Toraja people. This type of research is qualitative research with an ethnographic approach. The data in this study were taken by means of observation, interviews and documentation. The results showed: 1) The forms of Erong burrows found in the Tana Toraja area consisted of boats, mortar, buffalo and pigs. Differences in shape, size, cover form, decoration and orientation are strongly influenced by factors of belief, social stratification, mass and natural conditions around them. 2) The meaning of the erong carvings as a sign of hope for the ancestors, a sign that a person is smart and wise, a sign of courage, nobility and nobility, an appreciation, a meaning as a warning to society, a sign that symbolizes wealth or glory, the meaning that to link property to the house must be in an honest way and need cooperation within the family or community, meaning as a symbol of the greatness of the Toraja nobility. The findings of this study can help the development of disciplines in the field of cultural geography and as an inventory of existing national cultures, especially the diversity of symbolic meanings of erong.Â